GAMBARAN PERILAKU PEMBERIAN MAKANAN, STATUS GIZI DAN PENYAKIT INFEKSI PADA BAYI USIA 0-6 BULAN DI WILAYAH KERJA PUSKESMAS DATUK BANDAR KOTA TANJUNGBALAI TAHUN 2017 - Gusmaini Ahmad Hasibuan; Jumirah .; Zulhaida Lubis (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2018)
The most appropriate food for babies 0-6 months is breast milk. However, in practice there are still many who provide food other than breast milk. Early feeding can lead to infants more susceptible to disease, especially infectious diseases and in the long run can cause degenerative diseases. The purpose of this research was to know the description of mother’s feeding behaviour, nutritional status and infectious disease 0-6 months infansts in working area of Datuk Bandar Health Center Tanjungbalai city in 2017. The research type was survey with descriptive analysis and cross sectional design. Samples were 0-6 months baby as much 65 babies living in the working area of Datuk Bandar Health Center Tanjungbalai city, was obtained using proportional random sampling technique of 5 urban-villages. Data collection was done by direct interviews on mothers through questionnaires. The results showed the behavior of infant feeding 0-6 months in the work area of Datuk Bandar Health Center based on mother knowledge 64,6% in good category, mother attitude 64,6% in less good category and mother action 90,8% in less good category. Nutritional status of infants aged 0-6 months based on WAZ 87.7% of infant in normal category. Based on the LAZ 52.3% of infants in normal category and 27.7% of infants stunting. While based on WLZ 46.2% of infants in normal category and 26% of obese, and 27.6% wasting. 52.3% of infants were exposed to respiratory infection and 64.6% were exposed to diarrhea. As many as 90.8% of mothers have provided food other than breast milk in infants aged 0-6 months. The reason the mother gave food other than breast milk were worries that breast milk was not enough and the child became thirsty (79.7%). It is recommended to Datuk Bandar Health Center staffs to do counseling about exclusive breastfeeding and proper infant feeding, counseling about the disadvantage if the baby is exposed to respiratory infection and diarrhea, measuring the length of the body so that the stunting problem can be overcome as early as possible and involving husbands role and community leader in order exclusive breastfeeding program can be complemented. Keywords: Feeding behaviour, Nutritional Status, Infectious Diseases, Infants 0-6 Months